2014
DOI: 10.1007/s15010-014-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for linezolid-associated thrombocytopenia in adult patients

Abstract: ObjectivesThrombocytopenia (TP) is a common adverse effect of linezolid (LZD). However, risk factors for LZD-associated TP have been reported in Western patients with relatively heavy body weight. The aim of this study was to determine the risk factors for LZD-associated TP in Asian population.Materials and methodsA retrospective cohort study was conducted among 101 consecutive patients who received LZD therapy (1,200 mg/day) between July 2003 and December 2013 at a tertiary referral hospital in Tokyo, Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 34 publications
6
75
3
2
Order By: Relevance
“…10 Thrombocytopenia is a common adverse effect in adult patients and the incidence of linezolidrelated thrombocytopenia has been reported about 15-50%. 7,11,12 The other common drugrelated side effects reported with linezolid therapy were diarrhea, nausea, headache, neuropathy, and abnormal liver function tests. 13 These adverse effects were mostly detected in patients receiving linezolid for longer than 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Thrombocytopenia is a common adverse effect in adult patients and the incidence of linezolidrelated thrombocytopenia has been reported about 15-50%. 7,11,12 The other common drugrelated side effects reported with linezolid therapy were diarrhea, nausea, headache, neuropathy, and abnormal liver function tests. 13 These adverse effects were mostly detected in patients receiving linezolid for longer than 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia was defined as either a platelet count of <150 x 10 9 /L or 50% reduction in platelet count from baseline level at initiation of linezolid therapy. 7 Outcomes of the patients based on the response to linezolid treatment were defined as cure, improved or failed. Cure was defined as the resolution of clinical and laboratory findings of infection for which linezolid were administered.…”
Section: Original Articlementioning
confidence: 99%
“…Prolonged treatment duration [7], renal insufficiencies [8], chronic liver disease [8] and lower body weight [2] have been reported as possible risk factors for linezolid-induced thrombocytopenia. Additionally, Natsumoto et al showed that both higher daily dose (mg/kg/day) (prevalence of thrombocytopenia; <17 mg/kg/day (17%), 17 -22 mg/kg/day (34%), 22 -27 mg/kg/day (48%), >27 mg/kg/day (72%)) and elevated serum creatinine were significant risk factors for linezolid-induced thrombocytopenia in non-hemodialysis patients [9]. However, we usually administer linezolid with usual dosage (600 mg q12 h) to hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…La trombocitopenia se definió como recuento de trombocitos de < 150 x 10 9 /l o una reducción del 50% en el recuento de trombocitos respecto del valor basal al inicio del tratamiento con linezolida. 7 Los desenlaces de los pacientes se definieron como cura, mejoría clínica o fracaso según la respuesta al tratamiento con linezolida. La cura se definió como la resolución de las manifestaciones clínicas y de laboratorio de la infección para la cual se administró la linezolida.…”
Section: Materiales Y Métodosunclassified
“…10 La trombocitopenia es un efecto adverso frecuente en los pacientes adultos y, según se ha señalado, la incidencia de trombocitopenia relacionada con linezolida ha sido del 15% al 50%. 7,11,12 Los otros efectos secundarios frecuentes que se publicaron en relación con el tratamiento con linezolida fueron diarrea, náuseas, cefalea, neuropatía y pruebas funcionales hepáticas anormales. 13 Estos efectos adversos se detectaron mayormente en los pacientes que recibieron linezolida durante más de dos semanas.…”
Section: Figura 1 Efectos Adversos Acumulados Durante Los Días De Trunclassified